Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1152/jn.00168.2002
|View full text |Cite
|
Sign up to set email alerts
|

Summation of Forces From Multiple Motor Units in the Cat Soleus Muscle

Abstract: Nearly all muscle models and most motor control concepts assume that forces from individual muscle fibers and motor units sum in an additive manner once effects of in-series tendon compliance are taken into account. Due to the numerous mechanical linkages between individual fibers, though, it is unclear whether this assumption is warranted. This work examined motor unit force summation over a wide range of muscle forces in the cat soleus. Nonadditive summation implies a nonlinear summation of motor unit forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…We concluded that force summation was limited, at least in part, by high series elastic compliance affording significant internal shortening and, therefore, a progressive loss in force-generating capacity according to the known force-length (Gordon et al, 1966) and force-velocity (Fenn and Marsh, 1935) properties of muscle. A similar reduction in force summation has been demonstrated during tetanic contractions when individual parts of whole muscle are stimulated simultaneously, rather than individually, and is likely owing to the common in-series elastic compliance allowing a higher amplitude and velocity of shortening (Sandercock, 2000;Perreault et al, 2003). Despite numerous examples of human and animal lower limb muscles experiencing significant internal shortening under constant-length conditions (see Roberts, 2002), the role the history dependence of force generation (Abbott and Aubert, 1952) plays in reduced force summation has received relatively little attention.…”
Section: Introductionmentioning
confidence: 58%
“…We concluded that force summation was limited, at least in part, by high series elastic compliance affording significant internal shortening and, therefore, a progressive loss in force-generating capacity according to the known force-length (Gordon et al, 1966) and force-velocity (Fenn and Marsh, 1935) properties of muscle. A similar reduction in force summation has been demonstrated during tetanic contractions when individual parts of whole muscle are stimulated simultaneously, rather than individually, and is likely owing to the common in-series elastic compliance allowing a higher amplitude and velocity of shortening (Sandercock, 2000;Perreault et al, 2003). Despite numerous examples of human and animal lower limb muscles experiencing significant internal shortening under constant-length conditions (see Roberts, 2002), the role the history dependence of force generation (Abbott and Aubert, 1952) plays in reduced force summation has received relatively little attention.…”
Section: Introductionmentioning
confidence: 58%
“…It should be acknowledged that nonadditive (nonlinear) summation has been reported in the cat soleus muscles. 24 This nonlinear effect may influence the resultant EMGforce relation.…”
Section: Limitation Of Muscle Force Modelmentioning
confidence: 99%
“…This effect is independent of the modifications of electrophysiological fiber properties. Moreover, the twitch forces summate nonlinearly (37,38), depending on the number of active motor units (37). A superadditive summation occurs with a small number of recruited motor units (37).…”
Section: Twitch Torquementioning
confidence: 99%
“…Moreover, the twitch forces summate nonlinearly (37,38), depending on the number of active motor units (37). A superadditive summation occurs with a small number of recruited motor units (37). Although unlikely, since the joint force did not change in the different contractions, it cannot be excluded that the change in temperature affected the nonlinearity in twitch summation.…”
Section: Twitch Torquementioning
confidence: 99%